2014
DOI: 10.1111/epp.12095
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary Hymenopteran parasitoids of scale insects (Homoptera: Coccoidea) in fruit orchards in Syria

Abstract: A survey for primary and secondary Hymenopteran parasitoids of scale insects (Homoptera: Coccoidea) in fruit orchards (apple, plum, date, olive, fig, citrus), was conducted in Syria during 2009–2012. Thirty three species of parasitoids belonging to the families Aphelinidae, Encyrtidae, Eulophidae and Pteromalidae were recorded as parasitoids on scale insects. Thirty two of these were primary parasitoids and one was a hyperparasitoid. The family with the greatest number of genera and species is Encyrtidae with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In Türkiye, Ülgentürk (2001), Ülgentürk et al (2004), and in Iran, Fallahzade and Japoshvili (2017), reported that B. longipennis parasitizes E. tilae. Some studies conducted in Türkiye and abroad have shown that B. longipennis is aparasitoid of P. corni (Blahutiak 1972;Japoshvili & Karaca 2002;Japoshvili et al 2008b;Basheer et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In Türkiye, Ülgentürk (2001), Ülgentürk et al (2004), and in Iran, Fallahzade and Japoshvili (2017), reported that B. longipennis parasitizes E. tilae. Some studies conducted in Türkiye and abroad have shown that B. longipennis is aparasitoid of P. corni (Blahutiak 1972;Japoshvili & Karaca 2002;Japoshvili et al 2008b;Basheer et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Scale insects (including mealybugs) are considered as some of the most serious economic pest insects in many countries of the world including Syria (Basheer & Mahmalji, 2006;Basheer et al, 2014). Scale insects have been previously reported as pests on fruit trees, olive, citrus, date palm, ornamental plants, forest trees and agricultural crops (Balachowsky, 1948;Gullan & Cranston, 2005;Miller & Davidson, 2005;S ßis ßman & € Ulgent} urk, 2009;Ben-Dov et al, 2013).…”
Section: Introductionmentioning
confidence: 99%